Magdalene.co Sebagai Media Advokasi Perempuan - Eni Maryani; Justito Adiprasetio (FISIP Universitas Atma Jaya Yogyakarta, 2017)
The subordination of women intertwined with patriarchy culture in the society. Magdalene.co is one of online media to advocate women. The study tries to reveal Magdalane.co’s creative efforts in undertaking gender-sensitive journalism and advocacy journalism for women. Content analysis, interviews, and literature studies are conducted for collecting data. The results show that Magdalene. co offers new values and perspectives on women and raises range of issues including religion, beliefs, lifestyles, and social conditions. However, class bias is still evident in their articles, discussed issues are limited to public domain, and it is inconsistent in changing stereotype of women.